ANALISIS PRODUKSI, EKSPOR TEMBAGA INDONESIA KE JEPANG DAN PERTUMBUHAN EKONOMI SEKTOR PERTAMBANGANINDONESIA - Darwin, Ranti; Aimon, Hasdi; Syofyan, Efrizal (Program Studi Magister Ilmu Ekonomi, 2014)
The study aims to determine and analyze (1)the influence of price of copper, interest rate, domestic consumption of copper,capital and exports to copper production,(2) the influence of price of copper, interest rate, consumption domestic of copper, GDP Japan and copper production to exports,(3) the influence of domestic consumption of copper, capital and exports to Indonesian economic growthin mining sector,(4)Prospect the exports of copper Indonesian to Japan in 2014-2019 to Indonesian economic growthin mining sector. This study utilize a model of simultaneous equation by means of Two-Stage Least Square (TSLS) from 1979-2011. The study concluded that (1) price of copper, interest rate, domestic consumption of copper, capital and exports significantly affect the copper production.(2) price of copper, interest rate, domestic consumption of copper, GDP Jepang and copper productionsignificantly affect the exports.(3) domestic consumption of copper, capital and exports significantly affect the Indonesian economic growth in mining sector. (4) Prospect the exports of copper Indonesian to Japan in 2014-2019 have significantly affect the Indonesian economic growthin mining sector. Keyword: Price Of Copper, Interest Rate, Domestic Consumption Of Copper, GDP Japan, Capital, Copper Production, Exports and Indonesian Economic Growthin mining sector.